2011
DOI: 10.1007/s11274-011-0746-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification of high strength wastewater originating from bioethanol production with simultaneous biogas production

Abstract: In this study, purification of the wastewater from corn stover-based bioethanol production process with simultaneous biogas production was investigated in a combined system, which was based on thermophilic anaerobic digestion in a fluidized bed reactor (AFBR), an aerobic airlift loop reactor (ALR), and a biological aerated filter (BAF). High strength distillery wastewater and high ammonia nitrogen content pretreatment wastewater were used as the influents. In the thermophilic anaerobic process (54-55°C), the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…As the biodegradability of wastewater from 2G biorefineries could be compromised by inhibitors added (e.g., ammonia) or generated during the pretreatment process (e.g., furans, carboxylic acids, and aldehydes), , it is important to evaluate its implications on biorefinery sustainability. Due to the reduction in organic degradation and biogas production, both MPSP and GWP increased with decreasing f D (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the biodegradability of wastewater from 2G biorefineries could be compromised by inhibitors added (e.g., ammonia) or generated during the pretreatment process (e.g., furans, carboxylic acids, and aldehydes), , it is important to evaluate its implications on biorefinery sustainability. Due to the reduction in organic degradation and biogas production, both MPSP and GWP increased with decreasing f D (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the generation of biogas and the low electricity consumption, all biorefineries�regardless of their annual COD load�had a negative COD management GWP, confirming the previously discussed trend that the new design had lower GWPs than the no WWT design. As the biodegradability of wastewater from 2G biorefineries could be compromised by inhibitors added (e.g., ammonia) or generated during the pretreatment process (e.g., furans, carboxylic acids, and aldehydes), 6,66 it is important to evaluate its implications on biorefinery sustainability. Due to the reduction in organic degradation and biogas production, both MPSP and GWP increased with decreasing f D (Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to molasses‐based first‐generation (1G) ethanol production, where no pretreatment step is involved and wastewater is generated only from the fermentation stage, the 2G ethanol process is likely to generate large quantities (~10× ethanol volume) of high‐strength complex wastewaters from pretreatment, hydrolysis and fermentation–distillation stages 3 . However, existing research has reported the characterization and treatment of only 2G ethanol fermentation residues/wastewaters 4‐8 and no studies were found on treatment of wastewater fractions emerging from the pretreatment stage.…”
Section: Introductionmentioning
confidence: 99%
“…have determined that the application of ozonation for distillery wastewater favorably enhanced methane production and cumulative gas volumes. Studies have reported COD reduction up to 75% via anaerobic digestion, whereas the use of AOP pretreatment has been reported to improve COD reduction and color removal by up to 90% 6,8 …”
Section: Introductionmentioning
confidence: 99%